The Role of Arabic Poetry in Nahwu Rules - Ahmad Royani; Zakiyah Palaloi; Iis Susiawati; Ratna Yudia Amartiwi (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
In the golden era of Islam, poetry as a part of Arabic literature continued to develop and still exists today. Arabic poetry is widely used by nuhats as a source of taking nahwu rules. The purpose of this study is to reveal the role of poetry in taking the nahwu rules that are currently developing. This research employs descriptive qualitative research method. This research is a literature study related to the role of poetry in taking nahwu rules. The research data were analyzed by content analysis method with the aim of describing the content in detail. The results of the study show that sama’ has been one of the arguments/sources in creating rules in nahwu science. Sama’ is divided into three, they are the Qur'an, hadith and the sayings of Arabs in the poetry and prose. The poetry is widely used as hujjah or argument in nahwu rules by the nahwu scholars of various madzhabs, whether used as main arguments or supporting arguments, for which the main arguments are from the Qur'an and Hadith. Meanwhile, according to Arab scholars, literature occupies the third position as the most fluent Arabic language after the language of the Qur'an and Hadith. In addition to adding treasures in the study of Arabic literature, this research is expected to open more attention of Arab scholars to Arabic literary works such as poetry in developing easy nahwu rules. In addition, to add treasures to the study of Arabic literature, this research is expected to open more attention of Arab scholars to Arabic literary works such as poetry in developing easy nahwu rules.